Biblical translation in Chinese and Greek : verbal aspect in theory and practice - Foley, Toshikazu S. (Linguistic Biblical Studies, 2009)
This study integrates three independent subjects-translation theory, Mandarin aspect, and Greek aspect-for the purpose of formulating a working theory applicable to translating the Bible. The primary objectives are defined in terms of grammatical translation of Greek aspect into Mandarin aspect at the discourse level. A historical overview of the Chinese Bible is provided as a way of introducing major translation issues related to linguistic, conceptual, and logistical challenges. The proposed theory provides the translator with a powerful tool, which is tested in two sample passages from John 18-19 and 1 Corinthians 15. Provided, also, are critical reviews of over sixty Chinese Bible versions, Nestorian, Manichaean, Catholic documents, and a translation written according to the proposed theory.